2016
DOI: 10.1016/j.crad.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT and chemical-shift MRI for differentiating thymoma from non-thymomatous conditions in myasthenia gravis: value of qualitative and quantitative assessment

Abstract: Comparison of CT and chemical-shift MRI for differentiating thymoma from nonthymomatous conditions in myasthenia gravis: value of qualitative and quantitative assessment AIM: To evaluate the usefulness of computed tomography (CT) and chemical-shift magnetic resonance imaging (MRI) in patients with myasthenia gravis (MG) for differentiating thymoma (THY) from thymic lymphoid hyperplasia (TLH) and normal thymus (NT), and to determine which technique is more accurate. MATERIALS AND METHODS:Eighty-three patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…271 hyperplasia cases and 3% of the normal thymus cases [13]. Priola AM's study found that the mass form was found in 20/22 thymoma cases, and in 12/65 hyperplasia cases [6]. In our study, up to 34/37 (91.9%) thymoma were in mass form.…”
Section: Signs Distinguish Between Thymoma and Not Thymomasupporting
confidence: 55%
See 3 more Smart Citations
“…271 hyperplasia cases and 3% of the normal thymus cases [13]. Priola AM's study found that the mass form was found in 20/22 thymoma cases, and in 12/65 hyperplasia cases [6]. In our study, up to 34/37 (91.9%) thymoma were in mass form.…”
Section: Signs Distinguish Between Thymoma and Not Thymomasupporting
confidence: 55%
“…In the opposed-phase image (C), mass showed the absence of signal intensity loss relative to the in-phase image (D). CSR value were 0.68. logistic regression model for qualitative parameters and SII, Priola AM found that SII were significantly correlatedwith the probability of finding thymoma, because the probability of tumor presence decreased with increased SII (OR per 1% increase, 0.64; 95% CI: 0.71-0.58) [6]. Therefore, an increase 0.01 of value CSR or 1% of value SII for fixed age and gender leads to anincrease of 1.5 times and reduction of 36%, respectively, in the probability of finding thymoma.…”
Section: Logistic Regression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The features displayed via MSCT had good spatial and density resolution. The shape, edge, and surrounding tissues of nodules can be clearly and completely displayed with precision and reliability through thin‐layer reconstruction, providing important information for diagnosis . This study shows that thymic cysts and low‐risk thymomas with a maximum diameter of the anterior mediastinum of ≤ 3 cm possess smooth borders, indicating that they are more likely benign lesions.…”
Section: Discussionmentioning
confidence: 84%